Learning-based autonomous vascular guidewire navigation without human demonstration in the venous system of a porcine liver - Karstensen, Lennart; Ritter, Jacqueline; Hatzl, Johannes; Pätz, Torben; Langejürgen, Jens; Uhl, Christian; Mathis-Ullrich, Franziska (International journal of computer assisted radiology and surgery, 2022)
The navigation of endovascular guidewires is a dexterous task where physicians and patients can benefit from automation. Machine learning-based controllers are promising to help master this task. However, human-generated training data are scarce and resource-intensive to generate. We investigate if a neural network-based controller trained without human-generated data can learn human-like behaviors.